Critical Thinking As The Foundation Of Pedagogical Practice In University Teachers. (Journal of Pharmaceutical Negative Results, 2022)
The aim of the study was to examine the influence of different schools of thought on the pedagogical practices of university professors. The researchers used qualitative methods to collect information, such as interviews with experts and a wide range of real-world (multicase) examples. Professors from the various universities in Lima participated in the study, which used a questionnaire with open-ended questions and a field notebook to collect data. There is a lack of support for critical, analytical, reflective and even more creative thinking in the classroom based on the theoretical definitions of these skills, which can be seen in the various categories of data collection in this study. Despite the controversies, this methodology has allowed the generation of opinions and conclusions about the effects of these actions and will allow a perspective on the effects of the pedagogical procedures and the effects that the nonimplementation of corrective measures would have.